Cost-effectiveness of artemisinin combination therapy for uncomplicated malaria in children: data from Papua New Guinea - Wendy A Davis; Philip M Clarke; Peter M Siba; Harin A Karunajeewa; Carol Davy; Ivo Mueller; Timothy ME Davis
OBJECTIVE: To compare the cost-effectiveness of conventional antimalarial therapy with that of three artemisinin combination treatment regimens in children from Papua New Guinea aged 6 to 60 months. METHODS: An incremental cost-effectiveness analysis was performed using data from 656 children with Plasmodium falciparum and/or P. vivax malaria who participated in a large intervention trial in two clinics in northern Papua New Guinea. The children were randomized to one of the following groups: (i) conventional treatment with chloroquine plus sulfadoxine plus pyrimethamine (CQ+S+P); (ii) artesunate plus S plus P; (iii) dihydroartemisinin plus piperaquine (DHA+PQ); and (iv) artemether plus lumefantrine (A+L). For treatment outcomes, World Health Organization definitions were used. The cost of transport between home and the clinic plus direct health-care costs served as a basis for determining each regimen's incremental cost per incremental treatment success relative to CQ+S+P by day 42 and its cost per life year saved. FINDINGS: A+L proved to be the most effective regimen against P. falciparum malaria and was highly cost-effective at 6.97 United States dollars (US$) per treatment success (about US$ 58 per life year saved). DHA+PQ was the most effective regimen against P. vivax malaria and was more cost-effective than CQ+S+P. CONCLUSION: A+L and DHA+PQ are highly cost-effective regimens for the treatment of paediatric P. falciparum and P. vivax malaria, respectively, in parts of Papua New Guinea. Future research will be required to determine if these findings hold true for other territories in Asia and Oceania with similar malaria epidemiology.